The History of Nawa Gapura Marga Raja, The First Gate of Cirebon - Abdillah, F; Santosa, I; Sabana, S; Hasyim, R A O S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The gate is a building that during the Hindu and Buddhist times was part of the temple complex. gapura can be said to be an expression of expression related to the beliefs of its supporters. The gate is an architectural work that describes the cultural characteristics of a group of people. For Javanese people, the gate is treated with an understanding of tradition and belief, because it is the pattern and shape of the gate building structure by the Javanese cosmological tradition. This research uses a visual narrative method, to see the relationship between the past, present, and plans. Data collection through oral approaches, interviews, and literature studies. The results of this study show that the Nawa Gapura Marga Raja is a building that was founded by Pangeran Wangsakerta in 1677 AD, as a function of the entrance to Gotrasawala activities, then developed into the entrance to the harbormaster and secret door for the escape of the Keraton family members, and in the future, we must preserve it